Peranan Pendidik dalam Pembentukan Karakter Peserta Didik sebagai Upaya Pencegahan Tiga Dosa Besar Pendidikan di Sekolah Dasar - Daniel Dwi Saputra; Maria Natalisa; Dwi Nur Azizah; Supriyadi Supriyadi; Amrina Izzatika (Departement of Mathematics Education, 2024)
In assessing a person, one can observe the character of each individual. The three major sins of education are negative issues in education that include bullying, sexual violence, and intolerance. This research uses a qualitative method through literature study. (literature review). This literature review includes a search for relevant research articles, books, research reports, and other pertinent sources. The process begins with the processing of both primary and secondary sources, which are then interpreted to draw conclusions. Based on the research findings, it was obtained that in the formation of students' character, educators play a very important role. Some of the roles of educators are: Educators serve as role models; Educators serve as motivators; Educators serve as facilitators; Educators serve as evaluators; and Educators serve as inspirators. One of the efforts to shape the character of students is to take preventive measures against the three major sins of education, such as school habituation programs, like the routine of the red and white flag ceremony, literacy activities before starting lessons, regular healthy exercise routines, and routine religious activities.